Studies in Health Technology and Informatics Volume 12 - Knowledge and Decisions in Health Telematics - Barahona, P. (IOS Press, 2014)
Medical doctors are used to rely on technical devices for decision support for diagnosis and choice of treatment. Thus, if a phonocardiogram reveals a heart murmur which the physician did not hear in the stethoscope, he is more likely to mistrust his ear rather than the recording. Nevertheless, the same doctor will hesitate to use artificial intelligence or decision support from an expert system because of lack of confidence in its reliability except in very selected cases. He will claim that patients and diseases are so individual that a computer system is too crude an instrument to rely on, and right or wrong he might feel that a disagreement between his own judgement and that offered by the software might offer a legal problem, he would prefer to be without. Yet, the development of expert systems in medicine remains a real challenge and actually systems are being successfully used.